ANALYSIS OF THE PROFITABILITY RATIO EFFECT, MARKET VALUE RATIO, AND COAL PRICES TO STOCK PRICES OF COAL COMPANIES - Abdul Sani Sihotang; Anita Munir (Management and Leadership Study Programme, 2021)
This study aims to examine the effect of profitability ratios (EPS and NPM), market value ratios (PBV), and reference coal prices (HBA) on stock prices in 2009 - 2019. This study is a quantitative descriptive approach with the company chosen by ADRO, ITMG, and PTBA. The method of analysis used descriptive analysis and multiple linear regression analysis. Hypothesis testing uses the t-test to test the coefficient partially, and the Goodness of Fit test uses R2 (Coefficient of Determination) to test simultaneously. All variables have been tested using the classical assumption test. The results showed that all variables passed the classical assumption test and were suitable for research data. The statistical t-test results show that the variable earning per share ratio (EPS) partially has a significant and positive effect on stock prices. The ratio variable of net profit margin (NPM) partially has a significant and negative effect on stock prices. The price to book value (PBV) ratio variable partially has a significant effect on stock prices, and the reference coal price (HBA) partially has a negative but not significant effect on stock prices. Simultaneously, the ratio of Earning per Share (EPS), Net Profit Margin (NPM), Price to Book Value (PBV), and Coal Price (HBA) has a significant effect on stock prices. This is explained by Sig F. = 0,000 <Level of Significant = 0.05, and the value of R2 (coefficient of determination) is 92.8%, while other factors outside the model explain the remaining 7.2%. This research can be used by companies and investors who will invest.